1985
DOI: 10.1126/science.3918347
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Locations of the Murine T-Cell Receptor Alpha-Chain Gene and the T-Cell Gamma Gene

Abstract: Two independent methods were used to identify the mouse chromosomes on which are located two families of immunoglobulin (Ig)-like genes that are rearranged and expressed in T lymphocytes. The genes coding for the alpha subunit of T-cell receptors are on chromosome 14 and the gamma genes, whose function is yet to be determined, are on chromosome 13. Since genes for the T-cell receptor beta chain were previously shown to be on mouse chromosome 6, all three of the Ig-like multigene families expressed and rearrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…By contrast, all of the FXI-induced tumors examined lacked the 11-kb fragment (indicated by the top arrow). These results have some similarity with those of Kranz et al (21), who demonstrated an 11-to 16-kb rearrangement when analyzing CTL clones with a y-chain probe. However, it is unclear from our analysis that the missing 11-kb fragment resulted in the 16-kb fragment made by fusion of the V and C regions are observed by Kranz et al (21).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…By contrast, all of the FXI-induced tumors examined lacked the 11-kb fragment (indicated by the top arrow). These results have some similarity with those of Kranz et al (21), who demonstrated an 11-to 16-kb rearrangement when analyzing CTL clones with a y-chain probe. However, it is unclear from our analysis that the missing 11-kb fragment resulted in the 16-kb fragment made by fusion of the V and C regions are observed by Kranz et al (21).…”
Section: Resultssupporting
confidence: 89%
“…These results have some similarity with those of Kranz et al (21), who demonstrated an 11-to 16-kb rearrangement when analyzing CTL clones with a y-chain probe. However, it is unclear from our analysis that the missing 11-kb fragment resulted in the 16-kb fragment made by fusion of the V and C regions are observed by Kranz et al (21). In accordance with their findings, an additional rearrangement was noted, represented by the appearance of a 4.5-kb fragment (Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Chromosome Hybridization. Metaphase chromosome spreads from a murine myeloid cell line (CAK) or from normal human male peripheral blood lymphocytes stimulated with phytohemagglutinin were prepared as described (14). Hybridization of the lck probe to mitotic chromosomes was performed by a modification of the method of Harper and Saunders (15).…”
mentioning
confidence: 99%